Antiferromagnetism and ferromagnetism in layered 1T-CrSe_2 with V and Ti replacements - Freitas, Daniele C. (2013)
We have studied the effect of substitution of Cr in metastable 1T -CrSe2 by Ti and V on its structural and magnetic properties. The structural transitions observed between 165-180 K in the pure material are stomped by the doping. The pure compound has a magnetization corresponding to an antiferromagnetic (AF) ground state. On Ti substitution, we observe an increase of the lattice constants and a gradual passage towards a ferromagnetic state. While V replacement maintains AF up our highest doping, xV =0.5. With our experimental results and the help of first principles calculations we construct the phase diagram of the system.